Effect of Changes in Liver Blood Flow on the Pharmacokinetics of Saruplase in Patients with Acute Myocardial Infarction - van Griensven, Jean M T; Koster, Rudolph W; Hopkins, Gwynn R; Beier, Horst; Günzler, Wolfgang A; Kroon, Ria; Schoemaker, Rik C; Cohen, Adam F (Thrombosis and Haemostasis, 1997)
Background: The recombinant unglycosylated single chain urokinase-type plasminogen activator saruplase is cleared for a large part by the liver. A large interindividual variation in saruplase concentration is found in acute myocardial infarction (AMI) patients. The variable cardiac performance after an infarct may induce differences in liver blood flow that could explain the concentration diversity. This study was performed to investigate the relation between hepatic blood flow and the pharmacokinetic and pharmacodynamic properties of saruplase.Methods and Results: Thirteen AMI patients were enroled in this open label study. Patients received a bolus injection of 20 mg saruplase followed by a one-hour infusion of 60 mg saruplase. Concurrently 36 mg intravenous indocyanine green (ICG) was given over 1 h to measure hepatic blood flow. Blood samples were taken at regular time intervals to measure plasma levels of urokinase-type plasminogen activator (u-PA) antigen and activity, the two-chain form (tcu-PA) activity, indocyanine green, fibrinogen, fibrin and fibrin degradation products, α2-antiplasmin and thrombin antithrombin III complex. A correlation was seen between the clearance of ICG and both those of u-PA antigen (r = 0.62; p <0.05) and u-PA activity (r = 0.57; p <0.05). A negative correlation was seen between the area under the curve of tcu-PA activity and the areas under the effect curves of both fibrinogen and α2-antiplas-min (r = -0.84; p <0.01 and r = -0.65; p <0.05).Conclusions: Liver blood flow is an important determinant of the clearance of u-PA antigen and activity and reduction of flow in patients with heart failure will lead to an increase in plasma concentrations. High plasma concentrations of tcu-PA activity lead to increased systemic fibrinogenolysis. These results may be used to optimize saruplase treatment in patients with impaired cardiac function or after co-medication with drugs that affect liver blood flow.